ANALISIS PELAYANAN SPORT TOURISM DI SARANA OLAHRAGA UNIVERSITAS PENDIDIKAN INDONESIA SEBAGAI DAYA TARIK WISATA - Aprilia, Lu?luwatin Rosdiana (Jurnal Olahraga, 2019)
The purpose of this study is to determine the extent to which the Indonesian University of Education is able to provide tourist attraction for tourists who are currently trending as sports tourism.. The method used in this research is the method of dexcoective, the sample taken is 30 people using accidental sampling. The data analysis techniques in this study use SWOT analysis by maximizing strength and Opportunity (oppurtunities), but can simultaneously minimize weakness (weaknesses) and threats (threaths). SWOT analysis considers internal environmental factors in the form of strengths and weaknesses and external environment in the form of opportunities and threats faced by a tourist attraction. The results of internal factors evaluation of internal strength/potential and weakness of service owned by the University of Indonesia Education are able to utilize the existing strength factors to be able to overcome the factors of weakness. So that the University of Indonesia Education has a strong service of Sport Tourism as a wasata attraction in the city of Bandung. The results of the authors analysis by using an external matrix is able to utilize opportunities and avoid threats. So that the University of Indonesia Education has a potential enough opportunity to redevelop its service. Author's suggestion is to take advantage of the strategic location of UPI, optimizing the potential of its facilities, developing UPI as a sports tourism area, and as an athlete training and education Center and sporting event organizers.